Prognostic factors for successful extubation in newborns with congenital diaphragmatic hernia - Rannebro, A.; Mesas-Burgos, C.; Fläring, U.; Eksborg, S.; Berner, J. (Frontiers in Pediatrics, 2025)
IntroductionNeonates with congenital diaphragmatic hernia (CDH) have an associated high mortality and morbidity. The European CDH EURO consortium has developed guidelines for initial and perioperative ventilatory management. There are, however, no recommendations on how to wean these patients from the ventilator. Extubation failure is more frequent in this group of patients than in other neonates. The aim of this study was to describe patient characteristics and risk factors for failed extubation and to evaluate predictive factors for successful weaning.MethodsWe performed a retrospective study in a single centre tertiary pediatric intensive care unit in Stockholm, Sweden. CDH-patients (n = 38), aged 0–28 days, with extubation events were identified from 2017 to 2019. Eight patients (21.1%) needed reintubation within 24 h after the first extubation attempt. Patient demographics, surgical repair with patch, oxygenation saturation index (OSI), rapid shallow breathing index (RSBI), ventilatory settings, fluid balance and sedation on the day of extubation were recorded.ResultsPatients in the failed extubation group (FE) had lower birth weight (p < 0.05), surgical patch repair (p < 0.05), longer length of stay in intensive care (p < 0.05), longer time on the ventilator (p < 0.05) and other comorbidities (p < 0.001). Using logistic regression we identified OSI, RSBI and inspiratory pressure (Pinsp) as factors predicting a successful extubation, AUCROC 0.95 (95% CI: 0.87 to 1.00). Patients in the FE-group had significantly more often pulmonary hypertension requiring treatment (p < 0.05), a higher fraction of inspired oxygen (FiO2) (p < 0.05) and hypercapnia (p < 0.001) prior to extubation and an oxygen demand exceeding 40% two hours after extubation (p < 0.05).ConclusionUseful predictors of successful extubation in CDH patients are OSI, RSBI and Pinsp. Low birth weight, patch repair and comorbidity also appear to be important factors. Prospective studies are required to confirm findings in the present study.